Bentuk Ekspresi Emosional Tokoh Utama dalam Kumpulan Cerpen Lelaki-Lelaki Tanpa Perempuan Karya Haruki Murakami: Kajian Psikologi Sastra - Trylestari, Rizky; Muharudin, Eko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Literary works are imaginative creations of authors reflecting upon the social environment of life. Literary works arise from contemplating the meanings and essence of life experienced, felt, witnessed, and expressed. This study examines the forms of emotional expression of the main characters in the